PERANCANGAN DAN PEMBUATAN MOBILE LEARNING INTERAKTIF BERBASIS ANDROID DENGAN METODE PERSONAL EXTREME PROGRAMMING - Hidayat Rizal; Satriyo Adhy; Panji Wisnu Wirawan (Department of Informatics, Universitas Diponegoro, 2013)
Mobile Learning ( M - Learning ) is the learning by using mobile devices, regardless of time and place. M-Learning has the constraint that M-Learning users must connect to the internet to be able to get the learning content . With the Android device, that could be implanted a native application inside, allowing the M - Learning content stored on the device . This study examines how the native application can be developed with Personal Extreme Programming method. In addition , this study reinforces previous research that E-Learning can be expanded ability to be M-Learning. As an outcome of this study is a M-Learning application that utilizes E-Learning that has existed , in which M - Learning applications that have some capability of E - Learning that capture and store content on mobile devices , so that the content is not required to access the internet connection .